Zoom in on learning with a virtual microscope: A convergent parallel mixed-method study - Ava K. Chow; Nazlee Sharmin (PLoS ONE, 2025)
Knowledge of histology is essential for many disciplines in professional health education. Virtual Microscopes (VMs) are increasingly becoming popular as a cost-effective teaching tool for histology. However, a lack of hands-on experience with traditional light microscopes and glass slides concerns many educators. Although studies have reported improvement or no difference in students’ knowledge and/or performance using either virtual or optical microscopes, reports on the impact of VMs on students’ understanding of magnification and orientation are scarce. We conducted a convergent, parallel mixed-method study to assess dental students’ understanding of magnification and orientation after using a virtual microscope to study oral histology. Six hours of mandatory lab sessions and critical thinking assignment questions were designed for the 1st year students in the Doctor of Dental Surgery (DDS) program. Quantitative data were collected from students’ performance in orientation and magnification-related questions in the summative assessments. Students’ written responses to reflective questions were the qualitative data, analyzed using manifest content analysis. All 32 students accurately answered 3 out of 5 questions, requiring them to apply the knowledge of magnification and orientation. 30 and 29 students correctly answered the remaining questions, respectively. 97% of the class agreed to improve their understanding of magnification and orientation after using the VM. All (100%) students (n = 32) completed the reflective assignment, generating 64 meaning units. 17 codes were generated and compiled into seven subcategories, which were further condensed into two categories: refinement of mental models and enhanced learning. Although our study is limited by a small sample size, it sheds light on the strategies adopted by dental students to improve their senses of magnification and orientation while using a VM.